2010
DOI: 10.1371/journal.pone.0008892
|View full text |Cite
|
Sign up to set email alerts
|

Using Small-Scale Studies to Prioritize Threats and Guide Recovery of a Rare Hemiparasitic Plant: Cordylanthus rigidus ssp. littoralis

Abstract: BackgroundRecovering endangered species would benefit from identifying and ranking of the factors that threaten them. Simply managing for multiple positive influences will often aid in recovery; however, the relative impacts of multiple threats and/or interactions among them are not always predictable. We used a series of experiments and quantitative observational studies to examine the importance of five potential limiting factors to the abundance of a state-listed endangered hemiparasitic annual forb, Cordyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Deer at FONR clearly affected some plants, such as Ceanothus in this study, oaks ( Q. agrifolia ; L. R. Fox, unpublished), and the endangered annual seaside bird's beak, Cordylanthus rigidus ssp. littoralis (Watts et al, 2010), but there have been no reported extirpations.…”
Section: Discussionmentioning
confidence: 99%
“…Deer at FONR clearly affected some plants, such as Ceanothus in this study, oaks ( Q. agrifolia ; L. R. Fox, unpublished), and the endangered annual seaside bird's beak, Cordylanthus rigidus ssp. littoralis (Watts et al, 2010), but there have been no reported extirpations.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple life history stages must be supported to ensure long-term survival (Jackson et al 2009) and an extensive literature points to factors that could limit rare plant recovery at various phenophases. These include restricted geographic range and narrow habitat requirements (Schemske et al 1994), seed predation (Watts et al 2010;Combs et al 2013;Leja et al 2015;Kurkjian et al 2017), herbivory (Joe and Daehler 2008;Watts et al 2010;Hill Bermingham 2010;Grossenbacher et al 2018), fire suppression (Kaye et al 2001;Paniw et al 2015), water stress (Traveset et al 2003), pollen limitation (Knight et al 2005), partial male sterility that reduces self-compatibility and favors outcrossing with sterile male individuals (Fernández-Illescas et al 2010), lack of pollinators (Schurr et al 2019), and competition with invasive species (Grewell et al 2003;Fiedler et al 2007;Watts et al 2010;Reynolds and Boyer 2010;Schneider 2013). Restricted geographic range, narrow habitat requirements, unknown interactions with pollinators, and partial male sterility are important considerations for the survival and growth of S. californica.…”
Section: Fish and Wildlife Service 2013; Unpublished Boyer Lab Surveys)mentioning
confidence: 99%